2017
DOI: 10.1084/jem.20161375
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis imprints heterogeneity in tissue-resident macrophages

Abstract: Macrophages are important for tissue function, and adapt phenotypically to each tissue by factors produced locally. A-Gonzalez et al. now show that phagocytosis of unwanted cells additionally contributes to imprinting macrophage heterogeneity, thus promoting tissue homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(203 citation statements)
references
References 66 publications
11
191
1
Order By: Relevance
“…A). Phagocytosis is a mechanism to imprint distinct pathways of tissue macrophages and has been linked to fibrosis resolution in the liver . MoMF and Kupffer cells both up‐regulate inflammatory cytokines such as Il1b and Tnfa , which have been shown to promote the survival of HSCs and thereby to contribute to liver fibrosis .…”
Section: Resultsmentioning
confidence: 99%
“…A). Phagocytosis is a mechanism to imprint distinct pathways of tissue macrophages and has been linked to fibrosis resolution in the liver . MoMF and Kupffer cells both up‐regulate inflammatory cytokines such as Il1b and Tnfa , which have been shown to promote the survival of HSCs and thereby to contribute to liver fibrosis .…”
Section: Resultsmentioning
confidence: 99%
“…Phagocytosis has recently been demonstrated to imprint a distinct anti-inflammatory profile in tissue-resident macrophages and this occurred in part due to phagocytosis of neutrophils 43 . However cardiac tissue resident macrophages were not included in this study so the extent that this occurs in the heart is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…iPSDMs derived from this protocol showed higher endocytosis and efferocytosis capacities than PBDMs (Cao et al., 2019), indicating a more tissue‐resident macrophage‐like identity (A‐Gonzalez et al., 2017; Swirski, Robbins, & Nahrendorf, 2016). In addition, it has been shown that iPSDMs can be conditioned by neuronal cells to acquire a microglia identity in vitro (Haenseler et al., 2017; Takata et al., 2017).…”
Section: Commentarymentioning
confidence: 99%